Pendekatan Kepemimpinan Kepala Desa dalam Pembangunan Kanal Banjir Berbasis Partisipatif (Studi pada Desa Seumberkedawung Kecamatan Leces Kabupaten Probolinggo) - Agoestine, Fitriyana Yuanita (Jurnal Administrasi Publik, 2016)
Abstract: The Style of Leadership of the village in the contruction of flood canal village participatory based (The Study in Sumberkedawung Village, Subdistrict ofÂ  Probolinggo, City of Probolinggo). The village head at the village level is expected to run the government the village well in providing services to the community, so that if the village head showed a good performance then berpengaruhpada work at the district, provincial and national level. Leadership model is closely connected with the goals to be achieved by a village government. The purpose of this study to determine the model village head's leadership in the development of flood canal village fair. Results from the study that the leadership model village head Sumberkedawung fair to make people like the leader and development - another development that is not only a spillway into developing a variety of creative and programs undertaken by the village head Sumberkedawung. Keyword: Democratic Leadership Style, Community Participation, Rural Development Abstrak: Pendekatan Kepemimpinan Kepala Desa dalam Pembangunan Kanal Banjir Berbasis Partisipatif (Studi pada Desa Seumberkedawung Kecamatan Leces Kabupaten Probolinggo). Model kepemimpinan erat hubungannya dengan tujuan yang hendak dicapai oleh suatu pemerintahan desa. Tujuan penelitian ini untuk mengetahui model kepemimpinan kepala desa dalam pembangunan kanal banjir desa yang adil. Hasil dari penelitian bahwa model kepemimpinan kepala desa Sumberkedawung yang adil membuat masyarakat menyukai pemimpinnya dan pembangunan â€“ pembangunan yang lain tidak hanya kanal banjir menjadi berkembang dengan berbagai kreasi dan program yang dilakukan oleh kepala desa Sumberkedawung. Kata Kunci : Gaya Kepemimpinan Demokratis, Partisipasi Masyarakat, Pembangunan Desa